The Medium and Long Term Load Forecasting Combined Model Considering Weight Scale Method - Fan Li; Zhou Buxiang; Chen Shi; Li Zuo; Yang Changyu (Institute of Advanced Engineering and Science, 2013)
A combined model which adopted thought of weight scale method in load forecasting to remedy such defect was proposed according to the shortcomings of traditional load forecasting combined model. Adopting the logarithmic least square algorithm to get the weight of single forecasting model by using the relationship between scale judgment matrix and weight matrix, the new model could give out forecasting result through creating such scale judgment matrix and weight matrix. The theory and implementation details of new model are presented, calculating and application in practice power grid proves the model has the ability to improve load forecasting precision effectively compared with single forecasting model and traditional combined model. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2403